Bandar Udara Internasional Jawa Barat (BIJB) dan Potensi Kertajati Sebagai Aerocity - Tri Tjahjono; Eny Yuliawati (Research and Development Agency of The Ministry of Transportation, 2017)
Pemerintah Provinsi Jawa Barat telah menetapkan untuk mengembangkan Bandar Udara Internasional Jawa Barat (BIJB) di Kertajati, Kabupaten Majalengka dan menjadikan tata ruang kawasan sekitarnya terintegrasi menjadikan kota bandar udara (aero-city). Penelitian ini membahas pengembangan sebuah kota bandar udara atau aerotropolis bendasarkan studi literatur (meta analisis) yang kemudian dikaitkan dengan konsep tata ruang Kertajati maupun konteks Kota Cirebon Raya dan permasalahan maupun potensi yang ada. Di dalam pengelolaannya, dikarenakan sumber pembiayaan dari pemerintah pusat, maka perlu dibuat Badan Pelayanan Umum (BLU) untuk penanganan bandara dan PT. BIJB dibentuk oleh Pemerintah Provinsi Jawa Barat untuk menangani kawasan sekitarnya agar konsep Aero-City dapat terwujud. Kemitraan Pemerintah dengan Badan Usaha (KPBU) juga dimungkinkan baik di fasilitas ke bandar-udaraan maupun fasilitas penunjang. [West Java International Airport and The Potential of Kertajati as The Aerocity] West Java Provincial Government has decided to develop West Java International Airport (BIJB) in Kertajati, Majalengka Regency, and plan to integrate its surrounding region as an aerocity. This paper discusses the development of an airport as a city, or aerotropolis, based on literature review (meta analysis) which is then associated with the concept of Kertajati spatial management as well as the context of Greater Cirebon Area and the existing problems as well as the potential. Since the central government acts as a financing source, it is important to establish a public service agency that will support the management of airport within its technical part while the BIJB enterprise, that is formed by West Java Provincial Government will be focused to actualize the concept of aerocity. Therefore the partnership of the Government with Business Entities is also possible both in airport facilities or airport supporting facilities.